MODALITY AS A FUNCTIONAL-SEMANTIC CATEGORY - Yunusaliyev Boburkhon Tulkinjon ugli (Bright Mind Publishing, 2025)
This article provides a comprehensive theoretical analysis of the linguistic category of modality, paying special attention to its conceptualization in the traditions of Uzbek and Russian linguistics. In the study, using descriptive-comparative and analytical methods, well-known linguists, including Sh.Rakhmatullayev, Y.Mirzaahmedova, S.Saidov, J.Yakubov, V.Vinogradov, O.Akhmanova. Analyses show that in Uzbek linguistics, modality is understood not only as a grammatical category of mood of verbs, but also as a broader semantic and pragmatic category reflecting the speaker’s subjective state, including certainty, doubt, desire, and evaluation. In the research, modality was studied as a complex phenomenon expressing the speaker’s attitude to the content of the sentence and his attitude to reality.
Keywords: modality, modal meaning, modal words, linguistic semantics, pragmatics, mood, subjective evaluation, communicative intention